2009
DOI: 10.1111/j.1365-2249.2009.04004.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased immunoglobulin A in alcoholic liver cirrhosis: exploring the response of B cells to Toll-like receptor 9 activation

Abstract: Summary Alcoholic liver cirrhosis (ALC) is characterized by increased circulating levels of immunoglobulins (Igs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 43 publications
0
46
0
3
Order By: Relevance
“…Decompensated cirrhotic patients exhibited increased IgG levels in all etiologies, but alcoholic cirrhotic patients specifically exhibited a more profound elevation of IgA (HCV vs ALC, CIR comp , P = 0.0006, and CIR decomp , P = 0.0005). We postulate that TLR9 signaling may be the dominant driver of IgA class switching as previously reported . It is unlikely that alcohol itself drives Ig production or IgA class switching because patients with advanced non‐cirrhotic alcoholics, chronic pancreatitis did not manifest IgG or IgA elevations (IgG: 1176 ± 256.5, IgA: 238.1 ± 75.1, and IgM: 107.1 ± 28, n = 10).…”
Section: Discussionmentioning
confidence: 76%
“…Decompensated cirrhotic patients exhibited increased IgG levels in all etiologies, but alcoholic cirrhotic patients specifically exhibited a more profound elevation of IgA (HCV vs ALC, CIR comp , P = 0.0006, and CIR decomp , P = 0.0005). We postulate that TLR9 signaling may be the dominant driver of IgA class switching as previously reported . It is unlikely that alcohol itself drives Ig production or IgA class switching because patients with advanced non‐cirrhotic alcoholics, chronic pancreatitis did not manifest IgG or IgA elevations (IgG: 1176 ± 256.5, IgA: 238.1 ± 75.1, and IgM: 107.1 ± 28, n = 10).…”
Section: Discussionmentioning
confidence: 76%
“…In humans, serum IgA is reported to have both anti-inflammatory and pro-inflammatory roles [15], which could play a part in the pathogenesis of liver disease such as ALD. A recent report also showed that Toll-like receptor priming of B cells could account for the elevation of serum IgA in alcoholic liver cirrhosis patients [16]. On the other hand, there have been previous reports of increased serum IgA concentrations in diabetic patients [17].…”
Section: Discussionmentioning
confidence: 98%
“…demonstrated that altered Fc alpha R expression in monocytes leads to receptor saturation and increases the absolute level of IgA and IgA immune complex, due to defective clearance in alcoholic cirrhosis. Massonnet et al 74. demonstrated that enhanced IgA production by CpG led to activation of B cells in alcoholic liver cirrhosis, compared to the mechanism observed in healthy donors, and this was due to the intrinsic ability of these cells to produce more IgA.…”
Section: Immunological Dysfunction In Cirrhosismentioning
confidence: 98%